Influence of Waste Tire Rubber Particles Size on the Microstructural, Mechanical, and Acoustic Insulation Properties of 3D-Printable Cement Mortars - Matteo Sambucci; Marco Valente (Civil Engineering Journal, 2021)
3D printing technologies of construction materials are gaining ground in the building industry. As well documented in the literature, these advanced manufacturing methodologies aim to reduce work-related injuries and materials waste, enhancing architectural flexibility which would enable more sophisticated designs for engineering and aesthetic purposes. In this framework, the development of functional and eco-sustainable printable materials represents an extremely attractive challenge for research, promoting digital fabrication to reach its maximum cost-effective and technological potentials. The use of recycled tire rubber particles in 3D printable Portland-based compounds is an exclusive contribution in this field. This line of research aims to integrate the well-known engineering performances of rubber-cement materials with the advanced peculiarities of additive manufacturing methodologies. As an innovative contribution, the authors propose here a detailed study on the possible relationship between rubber particle size and technological properties of the 3D printable mix. Specifically, two groups of continuous size grading polymer aggregates (0-1 mm rubber powder and 1-3 mm rubber granules as fine and coarse fractions, respectively) were analyzed in terms of impact on rheology, print quality, microstructure, mechanical properties, and acoustic insulation performance. Concerning the print quality, rubber aggregates altered the fluidity of the fresh mix, improving the adhesion between the printed layers and therefore enhancing the mechanical isotropy in the post-hardening sample. A remarkable influence of the rubber gradation on the compounds’ behaviour was found in hardened properties. By comparing the rubberized compounds, the fine polymer fraction shows greater interfacial cohesion with the cement paste. However, more significant mechanical strength loss was found due to a greater reduction in density and increased porosity degree. On the other hand, mortars doped with larger rubber particles tend to have a higher unit weight, finest pore distribution, minor mechanical strength drop, and higher ductility but worse interface binding with the matrix. Regarding the acoustic insulation properties, a proper balance between rubber powder and granules in the mixes allows to obtain comparable/superior performance compared to plain mortar but the effect of the aggregate size is strongly dependent on the sound frequency range investigated. Future findings revolve around applicability studies of these formulations in civil and architectural fields, benefiting from the design flexibility of 3D printing. Doi: 10.28991/cej-2021-03091701 Full Text: PDF